Realizing the theoretical stiffness of graphene in composites through confinement between carbon fibers. (October 2018) - Chu, Jingwen; Young, Robert J.; Slater, Thomas J.A.; Burnett, Timothy L.; Coburn, Broderick; Chichignoud, Ludovic; Vuilleumier, Aurèle; Li, Zheling
Abstract: It is shown that approximately 2 wt% of graphene in the matrix of a unidirectionally-reinforced carbon fiber epoxy composite leads to a significant enhancement in mechanical properties. Particularly, it is found that the axial stiffness of the composites is increased by ∼10 GPa accompanied by an increase in axial strength of 200 MPa. X-ray computed tomography and polarized Raman spectroscopy have demonstrated that the graphene is predominately aligned parallel to the carbon fibers axes. Stress-induced Raman band shifts showed that the confined and self-aligned graphene is subjected to high levels of stress during axial deformation of the composite, with an effective Young's modulus of ∼825 GPa, approaching its theoretical value of 1050 GPa. This behavior has been modeled using the rule of mixtures and shear-lag analysis and it is demonstrated that highly-aligned graphene in a constrained environment between fibers gives significantly better mechanical reinforcement than graphene in conventional polymer-based nanocomposites.